2002
DOI: 10.1038/sj.gt.3301628
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated gene transfer of urokinase plasminogen inhibitor inhibits angiogenesis in experimental arthritis

Abstract: Plasmin is essential for metalloproteases activation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…We have previously shown that ATF and ATF-HSA inhibit plasminogen activation and uPA activity: 30.9% plasminogen activation with AdATF-HSA vs 20.8% with AdATF at MOI 100. 15 As shown in Figure 1b, K1-3-HSA, ES-HSA and Can-HSA conjugates appeared to be cytotoxic factors on HUVEC endothelial cells, as most of cells are destroyed 96 h after virus infection at MOI 600 comparing to AdCO1 control infection. Results following AdATF-HSA infection did not differ significantly from those obtained with AdCO1 infection.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…We have previously shown that ATF and ATF-HSA inhibit plasminogen activation and uPA activity: 30.9% plasminogen activation with AdATF-HSA vs 20.8% with AdATF at MOI 100. 15 As shown in Figure 1b, K1-3-HSA, ES-HSA and Can-HSA conjugates appeared to be cytotoxic factors on HUVEC endothelial cells, as most of cells are destroyed 96 h after virus infection at MOI 600 comparing to AdCO1 control infection. Results following AdATF-HSA infection did not differ significantly from those obtained with AdCO1 infection.…”
Section: Resultsmentioning
confidence: 79%
“…10 The ATF-HSA chimeric protein contains the native secretion signal and the first 135 residues of murine urokinase (uPA) linked to 586 residues of mature HSA. 15 Can-HSA describes the C-terminal NC1 domain of the human a2 chain of type IV collagen (Can, 24 kDa) fused with HSA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations